A simple equation to correct for gadolinium interference on plasma selenium measurement using inductively coupled plasma mass spectrometry. (May 2020) - Wilschefski, Scott; Baxter, Matthew; Pool, Gertruida
Background: The measurement of selenium in human plasma is useful to assess deficiency or toxicity. The presence of gadolinium in clinical samples following administration of certain contrast agents used for magnetic resonance imaging can cause a significant positive bias in selenium results when measured using quadrupole inductively coupled plasma mass spectrometry (Q-ICP-MS). Methods: A mathematical equation to correct for gadolinium interference was assessed using both patient samples and commercial quality control/external quality assurance (QC/EQA) materials spiked with gadolinium. Samples were analysed using an Agilent 7900 ICP-MS operated in 'narrow peak' (half-mass) mode. Accuracy was evaluated by comparing corrected selenium results with target concentrations. Results: Corrected results were found to be accurate at all gadolinium concentrations tested (2, 4, 10 and 20 mg/L). Average recoveries ranged from 97.4 to 106.5%. Results for QC/EQA materials were within specified target ranges. Within-run imprecision was <3%, and between-run imprecision was <4.3%, demonstrating robustness. Conclusions: The correction equation described here is a simple method to correct for gadolinium interference on plasma selenium measurement using ICP-MS. This approach eliminates the need for specimen recollections, and improves patient care by reducing laboratory turnaround times and preventing delays in diagnosis/treatment.